The way the mistery of the Mattei’s case was solved - Chiara Pozzi; Paolo Matteis; Graziano Ubertalli; Donato Firrao (Fracture and Structural Integrity)
Enrico Mattei, the President of the Italian oil conglomerate, ENI, was about to land in Milan Linate Airport on October 27, 1962 when his airplane crashed on the ground due to a then unexplained accident. The investigation, reopened more than 30 years later, implied complete re-examining of the theories on macroscopic and lattice deformations under high velocity waves emanating from a small charge explosion.Various macro- and micro-structural changes are induced by an explosion and by the resulting shear stresses in metals exposed to it. At the microstructural level multiple slip bands or mechanical twins, induced from the pressure wave caused by an explosion, can be observed. The occurrence of either ones depend on the type of metal, the pressure and the strain rate. The temperature wave may also cause surface alterations. Different situations regarding stainless steels, aluminium, copper and gold alloys are analysed.Calculations to evaluate which deformation mechanism is eligible for different FCC metals and alloys are reported. Results of field explosion experiments are incorporated into the evaluation of microstructural signs possibly induced on metal targets by an unknown explosive event.Revisited theories were applied to the Mattei forensic case, reaching the conclusion that the aircraft had fallen following an on board small charge explosion.